Colonization in Mediterranean old-fields: The role of dispersal and plant-plant interactions - García, A. (2017)
Journal of Vegetation Science 2016 Colonization in Mediterranean old-fields: The role of dispersal and plant-plant interactions ( Articles not published yet, but available online Article in press About articles in press (opens in a new window) ) García-Cervigón, A.I.ab , Velázquez, E.cd , Wiegand, T.de , Escudero, A.f , Olano, J.M.a a iuFOR - Department of Agroforestry Sciences Universidad de Valladolid ES-42004 Soria Spain b Department of Natural Sciences Universidad Técnica Particular de Loja 110107 Loja Ecuador c Centro Universitario de Coyhaique Universidad de Magallanes José Miguel Carrera 485 Coyhaique 5951380 Chile View additional affiliations Abstract Questions: How do the dominant species in a Mediterranean community (Juniperus sabina, Juniperus communis and Pinus sylvestris) colonize abandoned fields? At what rates? Does dispersal limitation shape species colonization patterns? Does J. sabina act as nurse plant for the other two species? If so, in which stages of development: seedlings and saplings or older individuals? Location: Abandoned crop fields in the Alto Tajo Natural Park, central-eastern Spain. Methods: We mapped all individuals of the three species in three 4-14-ha plots, and aged them using dendrochronology. Spatial patterns in 2000, 1980 and 1960 were reconstructed according to estimated ages in 2014. We used a battery of spatial point-pattern analyses to evaluate dispersal in junipers, dispersal in pines, and the role of J. sabina as nurse plant for the other two species. Results: Both junipers colonized earlier than pines, probably due to their more effective endozoochorous dispersal. Late-coming pines, once established, expanded faster due to their higher seed productivity. Recent recruits of J. communis and P. sylvestris showed a random relationship with J. sabina canopies, whereas spatial patterns of older individuals in relation to J. sabina canopies ranged from attraction (plot 2 and marginally plot 1), suggesting facilitation, to repulsion in plot 3. These differences in spatial patterns between plots could be related to a shift in dominant herbivores, from sheep (plots 1 and 2) to red deer (plot 3). Conclusions: Dispersal and plant-plant interactions drove colonization in Mediterranean old fields. The inclusion of a temporal perspective in the analysis of spatial patterns allowed the detection of shifting interactions between J. sabina and the other two species, depending on their life stage. This is a clear advance compared with the usual static analyses, as it provides additional clues to interpret the mechanisms and processes underlying their origin. © 2016 International Association for Vegetation Science.